Why we need to teach leadership skills to medical students: a call to action. Issue 1 (27th March 2019) - Ross, Simone Jacquelyn; Sen Gupta, Tarun; Johnson, Peter
Abstract : Health system reform models since the early 1990s have recommended leadership training for medical students, graduates and health workers. Clinicians often have leadership roles thrust on them early in their postgraduate career. Those who are not well trained in leadership and the knowledge that comes with leadership skills may struggle with the role, which can impact patient safety and create unhealthy working environments. While there is some literature published in this area, there appears to be little formal evaluation of the teaching of leadership, with scarcely any discussion about the need to do so in the future. There are clear gaps in the research evidence of how to teach and assess medical leadership teaching. In this paper, three leadership frameworks from Australia, Canada and the UK are compared in terms of leadership capabilities for a global view of medical leadership training opportunities. A literature review of the teaching, assessment and evaluation of leadership education in medical schools in Australia, the UK and America is also discussed and gaps are identified. This paper calls for an education shift to consider practical health system challenges, citing the mounting evidence that health system reform will require the teaching and rigorous evaluation of leadership methods. Opportunities for teaching leadership in the curricula are identified, as well as how to transform leadership education to include knowledge and practice so that students have leadership skills they can use from the time they graduate.